PERAN PEER COUNSELING DALAM MENANGANI PERILAKU MENYIMPANG DIKALANGAN REMAJA MASJID BAITURRAHIM DESA BALAK KECAMATAN SONGGON KABUPATEN BANYUWAN GI - Nur Hafifah (Jurnal At-Taujih, 2021)
This research is motivated by the occurrence of deviant behavior towards adolescents carried out by the youth of the Baiturrahim Balak mosque such as drinking liquor in the middle of the night, like to say dirty words to one friend with another friend and make noise at night. Society is restless with their behavior, and teenagers are also very influential on other teenagers.The focus of this study examines the factors that influence the occurrence of deviant behavior among adolescents at Baiturrahim Mosque, Balak Village, Songgon District, Banyuwangi Regency and the role of peer counseling in dealing with deviant behavior among adolescents at Baiturrahim Mosque, Balak Village, Songgon District, Banyuwangi Regency.In accordance with the focus of the research above, the purpose of this study is to find out what are the factors that influence the occurrence of deviant behavior among teenagers at Baiturrahim Mosque, Balak Village, Songgon District, Banyuwangi Regency and find out the role of peer counseling in dealing with deviant behavior among teenagers at Baiturrahim Mosque, Balak Village, Songgon District, Banyuwangi Regency. .This study uses qualitative research methods, namely a study that produces descriptive data in the form of written, spoken words from people and observed behavior, and data collection using observation, interviews, and documentation techniques.The results of this study found that there are factors that influence deviant behavior among teenagers at Baiturrahim Mosque, Balak Village, Songgon District, Banyuwangi Regency, namely: a). Social factors b). Community environmental factors c). family factors d). Lack of confidence factor e). Economic factors. The role of peer counseling in dealing with deviant behavior among teenagers at Baiturrahim Mosque, Balak Village, Songgon District, Banyuwangi Regency, namely: a). The role of peers as mentors b). The role of peers can provide new information c). The role of peers as motivators d). The role of peers as supporters e). The role of peers can fill the void.